Detection of back-scattered signal for optical fibre resonant scanner - Juwadi Prak Ser; Lee, Chia Cheng; Farah Shahrim; Ahmad Ashrif A Bakar; M. H. H. Mokhtar (Penerbit Universiti Kebangsaan Malaysia, 2019)
We report the development of optical fibre resonant scanner that was developed using two multi-mode optical fibres that are attached side-by-side, producing a cantilevered optical fibre scanner. The optical fibre is mounted on photodiode and a small piezoelectric disk using polymer. The piezoelectric disk is driven with a sinusoidal signal that will then vibrate the mounted optical fibre, producing a single axis scan line. This paper reports on experimental detection of the back-scattered signal through dual-numerical aperture conFigureuration and identification of fibre position from a single scan line with respect to the optical reflections from the apertured reflector. The apertured reflector used was a brass metal with 1 mm of diameter that is placed before the imaging lens as a mechanism to differentiate the position of scan line. The single scan was obtained at its maximum length of 4.8mm with resonant frequency of 2.033kHz. The back-scattered signal from a target object is coupled back into the cladding of the optical fibre. The cladding mode is then stripped and detected by photodiode. The back scattered signal from the aperture is used to differentiate the position of fibre between the aperture and the target object itself. Differences in the position of the slots resulted pulses with different height and width, allowing the two backscattered signals to be distinguished. The experimental result is verified and compared with the theory back-scattered signal produced by such scanner.